Vattendragsrestaurering i teorin och fiskinventering i praktiken - Baudou, Johan (2006)
Running water-pathways have played an important roll in Sweden and frequently been manipulated. One profound change was made during the period of logging when streams were cleared from obstacles as big boulders, sharp bends and side-streams. Dams and different constructions gave control of the stream water and the streams became channel-like with a homogen structure. This interference gave problems for many fish populations and resulted in a shortage of feeding habitat, over-wintering habitat, spawning habitat, unnatural flow regimes, sedimentation, unnatural temperature fluctuations. Many of these historical changes of the watersheds are now subjects for restoration, ie., bring back the streams to what we believed it was before the change. However, what once existed in terms of complexity is now gone and difficult toreplace. To make the best of forthcoming restoration it is recommended that managers: